USING SELECTED METHODS IN MANAGEMENT AS KEY FACTOR TO DEVELOPMENT IN TRANSPORT - Dicova, Jana; Ondrus, Jan (Doprava a spoje, 2012)
Application of benchmarking in management enables managers to gain valuable information on the current situation of enterprise, of the holdings or logistics centre and opportunities for improving the efficiency of inputs, process services and communication with the public.